Comparative Analysis of Theme Types in Recount Texts Between School and College Students - Indana Zulfa, Lale; Gunawan, Wawan (International Proceedings of Nusantara Raya, 2024)
This research was conducted to see the types of themes that appeared in the recount texts between school and college students. This research aims to describe the structure and the types of dominant themes in recount texts among school and college students. Theory of Gerot and Wignell are the theories used in this research. This research uses a qualitative descriptive design with data in the form of percentages. The result of this research shows that, in junior high school, the dominant themes used are topical (63.6%) and textual (43.4%), at senior high school, the dominant themes used are textual (50.3%), and topical (49.6%), at the college students, the dominant themes used are topical (62.9%) and textual (37.0%). From the entire recount text between schools and college students, the dominant type of themes is topical with a total of 353 themes, and textual with a total of 246 themes.